THE IMPACT OF CORPORATE SOCIAL RESPONSIBILITY REPORTING AND ENVIRONMENTAL EXPENDITURES ON FINANCIAL PERFORMANCE - Juniartin, Imas Tria; Aji, Seto Satriyo Bayu (Jurnal Akuntansi Bisnis, 2025)
Background: The influence of Corporate Social Responsibility (CSR) disclosure and environmental cost management on corporate financial performance has received greater attention in recent years. CSR has the ability to enhance corporate reputation, while effective environmental cost management is thought to improve corporate financial sustainability. However, the extent to which these two factors influence financial performance remains a question. Consequently, this study aims to complement the existing literature on relationship analysis.Objective: This study aims to analyse the effect of CSR Disclosure and Environmental Costs on the company's Financial Performance.Research Methods: This research employed a quantitative approach, utilising regression analysis to evaluate the impact of Corporate Social Responsibility disclosure and environmental cost management on corporate financial performance in healthcare industry sector companies.Research Results: This study found that CSR disclosure and environmental cost management significantly affect corporate financial performance, enhancing reputation and financial sustainability.Originality/Novelty of Research: The novelty of this study lies in the comprehensive analysis of the effect of Corporate Social Responsibility (CSR) disclosure and environmental cost management on corporate financial performance, which has not been extensively discussed in previous literature. This research provides new insights into the interaction of these two factors in the context of financial sustainability.